Calibrated Peer Review (CPR) Method: Improving Student Descriptions Writing Skills in Madrasah Ibtidaiyah - Hafidah Hafidah (IAIN Palopo, 2021)
Writing descriptions is a skill that has been taught in grade VI elementary schools such as MIN 6 Cilacap. The purpose of this study was to determine the effectiveness of the Calibrated Peer Review (CPR) method in students' writing learning. To answer the stated objectives, the research method used was pre-experiment using one class as the sample. The number of research samples was 40 students consisting of 21 male students and 19 female students. To see the effectiveness of the method in learning, researchers used the pre-test as a first step to measure students' abilities then post-test after giving the treatment. The results showed a significant effect on the pre-test and post-test scores where the initial score was a mean of 65.3 and the final score was an average of 72.5. There was a good effect on the results of learning to write student descriptions because of any significant development in teaching. Thus, the CPR method is effective in students' writing learning